2010
DOI: 10.1002/cmdc.200900339
|View full text |Cite
|
Sign up to set email alerts
|

Identification, SAR Studies, and X‐ray Co‐crystallographic Analysis of a Novel Furanopyrimidine Aurora Kinase A Inhibitor

Abstract: Herein we reveal a simple method for the identification of novel Aurora kinase A inhibitors through substructure searching of an in-house compound library to select compounds for testing. A hydrazone fragment conferring Aurora kinase activity and heterocyclic rings most frequently reported in kinase inhibitors were used as substructure queries to filter the in-house compound library collection prior to testing. Five new series of Aurora kinase inhibitors were identified through this strategy, with IC(50) value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…In this study, we have developed a novel pan-Aurora kinase inhibitor BPR1K653 and further demonstrated its efficacy in targeting various types of cancers in vitro . Our pervious x-ray co-crystallography studies had demonstrated the physical interactions between the precursor compound of BPR1K653 and Aurora kinases [42], and the current in vitro kinase inhibition study has confirmed the target specificity of BPR1K653. Consistent with the molecular changes observed in cells treated with Aurora-B kinase specific siRNA oligos and with different pan-Aurora kinase inhibitors such as VX680 and SNS-314 [14], [43], [44], BPR1K653 treatment also induces endo-replication of cells and reduces amount of phosphorylated Histone H3 present in cells.…”
Section: Discussionmentioning
confidence: 58%
“…In this study, we have developed a novel pan-Aurora kinase inhibitor BPR1K653 and further demonstrated its efficacy in targeting various types of cancers in vitro . Our pervious x-ray co-crystallography studies had demonstrated the physical interactions between the precursor compound of BPR1K653 and Aurora kinases [42], and the current in vitro kinase inhibition study has confirmed the target specificity of BPR1K653. Consistent with the molecular changes observed in cells treated with Aurora-B kinase specific siRNA oligos and with different pan-Aurora kinase inhibitors such as VX680 and SNS-314 [14], [43], [44], BPR1K653 treatment also induces endo-replication of cells and reduces amount of phosphorylated Histone H3 present in cells.…”
Section: Discussionmentioning
confidence: 58%
“…We have reported a lead compound with a furanopyrimidine core capable of inhibiting Aurora kinase activity (20,21). Using this structure as a scaffold, we synthesized (Fig.…”
Section: Synthesis and Characterization Of Ibpr Compounds Targeting Amentioning
confidence: 99%
“…Analysis of these set of compounds revealed that some had a hydrazone functional group embedded in them. We have already reported several compounds bearing hydrazone fragments as Aurora kinase inhibitors, including those with pyrazole rings [14,25]. The pyrazole-hydrazones reported in ref 25 could not be further developed due to their chemical instability.…”
Section: Library Preparationmentioning
confidence: 97%
“…The other submicromolar inhibitor 7, with an IC 50 of 852 nM, was identified by sub-structure searching of the database for the hit 3 identified in Libdock VS, and has a tricyclic pyrazole core. It should be noted that none of the hits 3-9 were tested/identified during our previous HTS database screening campaign [14,27].…”
Section: Structure-based Virtual Screening and Hit Identificationmentioning
confidence: 99%
See 1 more Smart Citation